2017
DOI: 10.1177/2192568217707182
|View full text |Cite
|
Sign up to set email alerts
|

Most Influential Literature in Spinal Tuberculosis: A Global Disease Without Global Evidence

Abstract: Study Design:Bibliometric review of the literature.Objective:This bibliometric analysis aims to give an overview of the most influential academic literature written on spinal tuberculosis.Methods:All databases included in the Thomson Reuters Web of Knowledge were searched for the most influential publications in spinal tuberculosis. The most cited articles published between 1950 and 2015, with the main focus on orthopedic surgery, were identified using a multistep approach, and a total of 100 articles were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This brings up the hypothesis that citations are not a sole indicator for quality [ 61 ]. The older an article is the longer it can gather citations, which could question the significance of older articles in the current literature [ 62 ]. The status on basic research and risk factors in the field of fragility fractures is not represented in this study due to the focus on clinical management in the selection process.…”
Section: Discussionmentioning
confidence: 99%
“…This brings up the hypothesis that citations are not a sole indicator for quality [ 61 ]. The older an article is the longer it can gather citations, which could question the significance of older articles in the current literature [ 62 ]. The status on basic research and risk factors in the field of fragility fractures is not represented in this study due to the focus on clinical management in the selection process.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 10 countries contributed to the 100 articles, and the most productive country was the United States, which was consistent to other bibliometric studies in the field of spine surgery. 33,34 The reasons for this could be closely related to the country's investment in scientific research and the efforts of researchers. In contrast, Asian countries make a relatively small contribution to the 100 most-cited articles, which indicated that there is still a large gap of scientific studies between Asian countries and Western developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…The CNS-TB research landscape has expanded rapidly over the years [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] . While analyses of publications related to spinal tuberculosis [9] , [10] , [12] , infectious meningitis [13] , and bacterial CNS infections in south-east asia [11] have been reported, a comprehensive map detailing the current intellectual and social structure of CNS-TB does not currently exist. Such a map would significantly benefit the field by identifying key research constituents, collaboration patterns, and geographical discrepancies.…”
Section: Introductionmentioning
confidence: 99%